Pembuatan Bokashi Limbah Pelepah Dan Daun Kelapa Sawit (Elaeis Guineensis Jacq) - Daryono (Jurusan Teknologi Pertanian Politeknik Pertanian Negeri Samarinda Kampus Sei Keledang Jalan Samratulangi, Kotak Pos 192 Samarinda 75123, 2020)
Midrib palm oil leaves which often stacked around palm oil trees have been underused by the society. The leaves have the potencial to be used as a bokashi material. The high number of leaves wasted during harvesting has instigated the utilization of the leaves. There were three treatments in this research: P1 (25 kg midrib and leaves + 6 kg chicken manure + 1 kg bran + 200 ml EM-4 + 20 l water + 2 kg palm sugar), P2 (25 kg midrib and leaves + 8 kg chicken manure + 2 kg bran + 300 ml EM-4 + 30 l water + 3 kg palm sugar), P3 (25 kg midrib and leaves + 10 kg chicken manure + 3 kg bran + 400 ml EM-4 + 40 l water + 4 kg palm sugar). In this research, the temperature, colour, smell, testure, pH, and time needed for bokashi to form were observed. The findings show that P2, P3, and P1 gave the best results on all parameters observed. P2 required 44 days, P3 49 days, and P1 52 days to form bokashi. Based on the colour, smell, and texture, P2, P3, and P1 have transformed into compost fertlizer on day req 35, 40, and 43 respectively. In regard to standar, P1 with COrganic of 29.96 and C/N ratio of 9.46 and P3 with C-Organic of 31.30 and C/N Ratio of 9.54 meet the Standard of Organic Fertilizer Quality based on Regulation of Minister of Agricultureno. 70 / Permentan / SR.140 / 10/2011. Nevertheless, in terms of macro elements of N, P, K, none of the treatments complied with the standar.